Characteristic Pattern of IL-17RA, IL-17RB, and IL-17RC in Monocytes/Macrophages and Mast Cells From Patients With Bullous Pemphigoid - Nesmond, Stéphane; Muller, Céline; Le Naour, Richard; Viguier, Manuelle; Bernard, Philippe; Antonicelli, Frank; Le Jan, Sébastien (Frontiers in Immunology, 2019)
Inflammation is largely implicated in bullous pemphigoid (BP), the most frequent skin auto-immune blistering disease. IL-17, essentially IL-17A/F, has been involved in blister formation through regulation of protease production and its specific serum profile within BP was related to disease outcome. However, relationships between IL-17 family ligands and receptors are quite complex with 6 different IL-17 isoforms and 5 different receptors. We here aimed at clarifying the contribution of the IL-17 axis in BP by characterizing not only the expression of IL-17 receptor (IL-17R) members within immune cells isolated from BP patients (PMNs, n=9; T-lymphocytes, n=10 and monocytes, n=10) but also the expression of IL-17 isoforms in sera (n=83) and blister fluid (n=31) of BP patients. We showed that at diagnosis IL-17RA and IL-17RC expression were significantly increased in monocytes isolated from BP patients as compared to those from control subjects (p=0.006 and p=0.016 respectively). Notably both IL-17RA and IL-17RC mRNA expression remained elevated in BP monocytes at time of relapse. We further demonstrated a significant increase of all IL-17 isoforms tested in BP blister fluid compared with BP serum (IL-17A, p<0.0001; IL-17A/F, p<0.0001; IL-17B, p=0.0023; IL-17C, p=0.0022; IL-17E, p<0.0001). Among all, IL-17B was the only cytokine for which a significant decreased concentration within blister fluid was observed in BP patients with severe disease compared to patients with moderate disease (P=0.012). We further evidenced a significant negative correlation between IL-17B levels and blister/erosion BPDAI subscore (r=-0.52, p=0.003). We finally identified mast cells as a potential target of IL-17B in lesional skin of BP patients. In conclusion, we showed here that IL-17RA and IL-17RC expression in monocyte was associated with disease activity, and evidenced in situ a negative correlation between BP disease activity and IL-17B, which effects could be mediated by IL-17RB expressed by mast cell in BP lesional skin.